Redesigning the UI/UX of a Mobile-Based Employee Presence Application at PT. Menara Indonesia Using the Design Thinking Method - Putri, Nabilah; Syaifuddin; Pratiwi, Dian (Penerbitan Universitas Trisakti, 2025)
A mobile-based presence application ensures accurate and efficient presence tracking. However, poor UI/UX can hinder productivity and user comfort. This study redesigns the UI/UX of PT. Menara Indonesia’s employee presence application using the Design Thinking method, which includes empathize, define, ideate, prototype, and test stages.The redesigned prototype was evaluated using the System Usability Scale (SUS), scoring 90 for administration and 80 for employees, indicating improved usability. The new design enhances comfort, efficiency, and ease of use, making the application more user-friendly. This study serves as a reference for future development in optimizing presence applications to better meet user needs.